Tajam ke Bawah, Tumpul Ke Atas: Paradoks Penegakan Hukum terhadap Koruptor - Rina Dwi Yanti Tampubolon (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Law enforcement in Indonesia continues to face various challenges, particularly in the context of eradicating corruption. The phrase